Burnout syndrome in peruvian dental students: a prevalence study - Ramírez-López, Ana Elizabeth (2024)
Aim: Burnout syndrome describes the state of long-term physical, emotional and mental exhaustion related to work. This syndrome can cause health problems related to stress, insomnia, cardiovascular and musculoskeletal diseases, including an increase in alcohol consumption and drug use. It is important to recognize the presence of the initial signs of this syndrome, therefore this study aimed to determine the prevalence of the burnout syndrome in peruvian dental students. Methods: The study was observational, cross-sectional, and descriptive. It was carried out from September to November 2018, and it included a total of 154 dental students of four universities of La Libertad region, surveyed by census method. Three were private universities and one was public. Burnout was evaluated through the Maslach Burnout Student Survey Questionnaire (MBI-SS). The results were presented in absolute and percentage frequencies, as well as confidence intervals, using double-entry tables. Results: It was found that 24.68% of the students (24.71% in male students and 24.64% in female students) presented burnout syndrome. The public university of Trujillo presented the highest percentage of affected students (47.37%). A prevalence of 53,90% of emotional exhaustion was also found among the students under evaluation. Conclusions: Almost a quarter of the students surveyed presented burnout. It was also observed that the public University of Trujillo had a higher percentage of burnout than the three private ones. The percentage of prevalence of the burnout syndrome according to sex was similar. However according to dimensions, emotional exhaustion presented the highest percentage.